KRIMINALISASI SOSIOLOGIS NIKAH SIRI - Iwan Zaenul Fuad; Agus Fakhrina; Abdul Aziz; Ahmad Rosyid (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2011)
However, Nikah Siri (unregistered marital) has been seen as a part of the social behavior, and lived in Indonesian society. This behavior often impact living condition of social structure. In another side, this social problem must be fixed with appropriate law-making system. The Act Plan of ìHukum Peradilan Agama Bidang Perkawinanî (RUU HPABP) was noted in commitment to criminalize the behavior. Some sounds of pro and anti toward this Act Plan nowadays, make this issues more interesting be reseacrhed. Applying symbolic interactionism approach and labelling theory, this study examined the criminalization issues on the Act Plan in social framework. The framework is critical to assume the effectiveness of law making process based on people participation. This research took place in Pekalongan District (the City and Regency of Pekalongan), which is noted for the ëhiddení large number of nikah siri practices. Results of the study revealed the social criminalization of Nikah Siri akin to kinds of peopleís perception toward the behavior. The hidden types of Nikah Siri (hidden from peopleís knowledge) had an effect on social construction to criminalize the behavior, but not the open one.